Bringing home the money: xenophobia and remittances. The case of Germany - Elke Holst; Andrea Schäfer; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The determinants of migrants' remittances are the subject of this study based on German SOEP data (2001-2006). In contrast to previous studies we analyze the motives for remittances not only for foreigners but also for the broader group of individuals with a personal migration background. Major findings are: First, concerns about xenophobia lead to higher remittances. Second, income and gender has no impact on the probability to remit. Third, the acquisition of German citizenship is positively related to the amount remitted. All in all, remittances seem to be part of a personal financial allocation scheme for risk reduction.
Keywords: F22; J61; D10; 330; Remittances; immigrant workers; household behavior; Rücküberweisung (Migranten); Migranten; Haushaltsökonomik; Ethnische Diskriminierung; Deutschland